The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1001/jamanetworkopen.2021.42057
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of SARS-CoV-2 Surveillance Testing Among Children and Childcare Workers at German Day Care Centers

Abstract: IMPORTANCEClosure of day care centers has been implemented globally to contain the COVID-19 pandemic but has negative effects on children's health and psychosocial well-being. OBJECTIVE To investigate the feasibility of surveillance among children and childcare workers and to model the efficacy of surveillance on viral spread prevention. DESIGN, SETTING, AND PARTICIPANTS This nonrandomized controlled trial was conducted at 9 day care centers in Wuerzburg, Germany, from October 2020 to March 2021. Participants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 31 publications
(34 reference statements)
3
20
0
1
Order By: Relevance
“…Nevertheless, our study is in line with the idea that hygiene measures and testing strategies during the early waves of Covid-19 contained the pandemic in elementary schools and daycare settings, particularly when the Bavarian incidence was high (i.e., phase II during the second wave). With systematic and comprehensive testing strategies ( 32 , 33 ), maintaining hygiene measures and increasing vaccination rates we may be in a better situation to face the currently prevailing Delta and Omicron variants without falling back to less sophisticated measures such as extensive and complete closing of schools and daycare facilities. Recent German studies have clearly pointed out the magnitude of side effects of school closures including a lack of opportunities to learn and socialize leading to an increased risk of psychiatric problems and chronic disease ( 4 , 34 ) as well as a rise in educational inequality ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our study is in line with the idea that hygiene measures and testing strategies during the early waves of Covid-19 contained the pandemic in elementary schools and daycare settings, particularly when the Bavarian incidence was high (i.e., phase II during the second wave). With systematic and comprehensive testing strategies ( 32 , 33 ), maintaining hygiene measures and increasing vaccination rates we may be in a better situation to face the currently prevailing Delta and Omicron variants without falling back to less sophisticated measures such as extensive and complete closing of schools and daycare facilities. Recent German studies have clearly pointed out the magnitude of side effects of school closures including a lack of opportunities to learn and socialize leading to an increased risk of psychiatric problems and chronic disease ( 4 , 34 ) as well as a rise in educational inequality ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…All 9 DCCs, covering approximately 20% of all DCC-attending children in the area, had participated in a previous surveillance study. 16 …”
Section: Methodsmentioning
confidence: 99%
“…Different sampling methods have been investigated (eg, anal or buccal swab, saliva, midturbinate swab), and pooling has been proposed to save resources. 13 , 14 , 15 , 16 …”
Section: Introductionmentioning
confidence: 99%
“…Surveillance for SARS2 has been recommended as a modality to limit transmission of infection from unvaccinated individuals with asymptomatic or pre-symptomatic infection [ 3 ]. While acceptance of long-term surveillance testing was extremely high among our study population as demonstrated by high adherence to collection and return of swabs, the utility of weekly surveillance by rtPCR in our population was of limited value because of our extremely low rate of detecting asymptomatic or pre-symptomatic infection in unvaccinated participants.…”
Section: Discussionmentioning
confidence: 99%
“…Periodic testing for SARS2 infection may detect asymptomatic or pre-symptomatic infections, which have been reported to represent a significant proportion of infections particularly amongst healthy populations without comorbidities [ 1 ]. Asymptomatic and pre-symptomatic infections may contribute to transmission, albeit less than symptomatic infection [ 2 ], and therefore surveillance has been recommended to detect such cases [ 3 ]. Weekly testing for SARS2 infection is recommended for United States federal government employees who are unvaccinated when transmission risk is medium or high to reduce work-place transmission [ 4 ].…”
Section: Introductionmentioning
confidence: 99%